2008
DOI: 10.1111/j.1420-9101.2008.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread unidirectional transfer of mitochondrial DNA: a case in western Palaearctic water frogs

Abstract: Interspecies transfer of mitochondrial (mt) DNA is a common phenomenon in plants, invertebrates and vertebrates, normally linked with hybridization of closely related species in zones of sympatry or parapatry. In central Europe, in an area north of 48°N latitude and between 8° and 22°E longitude, western Palaearctic water frogs show massive unidirectional introgression of mtDNA: 33.7% of 407 Rana ridibunda possessed mtDNA specific for Rana lessonae. By contrast, no R. lessonae with R. ridibunda mtDNA was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(145 citation statements)
references
References 74 publications
(105 reference statements)
8
136
0
1
Order By: Relevance
“…Thus, now in Russia and Ukraine P. ridibundus is described (Ananjeva et al, 1998), in Eastern Turkey -P. caralitanus (= R. caralitana) Arikan, 1988(Plötner, 2005Ayaz et al, 2006) (Plötner, 2005;Plötner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, now in Russia and Ukraine P. ridibundus is described (Ananjeva et al, 1998), in Eastern Turkey -P. caralitanus (= R. caralitana) Arikan, 1988(Plötner, 2005Ayaz et al, 2006) (Plötner, 2005;Plötner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of chromosome sets of lake frogs in Armenia (P. ridibundus) and Europe (R. fortis) (Schmid, 1978;Mészarós, Bartos, 1978;Bucci et al, 1990;Spasič-Bošković et al, 1999;Plötner, 2005;Plötner et al, 2008) reveals the differences in the number of chromosomal pairs and C-banding patterns localization, which can be explained as interspecifi c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More gene flow was observed from P. perezi into P. ridibundus than from P. ridibundus into P. prezi [Schmeller et al, 2005]. P. ridibundus likely derives a selective advantage and is able to increase its distributional range by incorporating mtDNA [Plötner et al, 2008] and nuclear genes [Schmeller et al, 2005] from other species via hybridogens. In order for gene flow to occur between the species through a hybridogen, there must be some intergenomic recombination .…”
Section: Polyploid European Water Frogs ( Pelophylax Esculentus Complex)mentioning
confidence: 99%
“…There is evidence that hybridogenesis can be a pathway for selective gene exchange between species through diploid hybridogenetic individuals. mtDNA of P. lessonae was found to have introgressed into several populations of P. ridibundus , but mtDNA of P. ridibundus was not found in P. lessonae [Plötner et al, 2008]. Using allozymes, Schmeller et al [2005] demonstrated that alleles can be exchanged between P. ridibundus and P. perezi through their hybridogen, P. grafi .…”
Section: Polyploid European Water Frogs ( Pelophylax Esculentus Complex)mentioning
confidence: 99%